Analysis of Dominant Methods and Media Used by Teachers in Social Studies Learning in Schools - Suharli Suharli; Muhammad Iksan (STKIP Taman Siswa Bima, 2024)
This research aims to analyze the dominant learning methods and media used by teachers in implementing social studies learning in the classroom. In this research the author used a quantitative descriptive research method with survey techniques conducted on 27 social studies teachers in Sumbawa district. Each of the 9 social studies teachers in eastern, central and western Sumbawa was given an open questionnaire. Analysis of questionnaire data was carried out using descriptive analysis, namely using the percentage formula. The results of the analysis show that the majority of teachers still seem monotonous in using learning methods and media. This means that teachers are not optimal in selecting and applying various methods and media in social studies learning at school. This is shown by the results that 100% of teachers predominantly use the discussion method and 62.96% of teachers predominantly use map media in learning.